The role of phenofibrate in the treatment of microvascular complications of type 2 diabetes mellitus - Larisa Viktorovna Koshel'; Tatiana Ivanovna Romantsova (Сахарный диабет)
Results of numerous studies give definitive evidence that phenofibrate affects activity of PPAR-a receptors in liver and thereby decreases the level oflipids responsible for the development of atherosclerosis (VLDL, small dense LDL); simultaneously, it increases the level of anti-atherogenic HDL.Activation of PPAR-a receptors in vascular cells decreases activity of inflammation markers, such as C-reactive protein, TNF-a, IL-6, fibrinogen,etc. These effects of phenofibrate eventually lead to reduced risk of macro- and microvascular diabetic complications.